DOP-MS: A Microservice-based Data Offloading Service with Support for Data Anonymisation - Silvestre, Vitória R. N.; Gomes, Francisco A. A.; Cândido, Adriano L.; Fernandes, Filipe; Rocha, Lincoln S.; Trinta, Fernando A. M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
Due to mobile devices' growing presence in our daily routine, mobile applications are becoming increasingly complex. They require more powerful processing capability and more extensive data storage, which characterizes a challenge when computational constraints of these devices are taken into account. Several software infrastructures proposed to help the development of mobile applications with data offloading features. However, they lack essential features for data offloading, such as configurable data synchronization policy models, privacy mechanisms for the offloaded data, and scalability and performance analyses. This work presents DOP, a solution to assist the development of mobile applications that use data migration, including contextual data, from mobile devices to a remote environment, based on a microservice architecture. The data offloading technique enables data migration into a remote environment, allowing (i) storage savings on the mobile device and (ii) sharing data among users. The experiments on DOP showed benefits in storage savings on mobile devices and new possibilities for inferring situations based on shared data from multiple users.